Uji Aktivitas Antioksidan dari Daun Kelor (Moringa oleifera) yang Diekstraksi Menggunakan Teknik Soxhletasi - Siti Nurjanah; Haeruddin; Nurlansi (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Antioxidant Activity Tests of Moringa (Moringa oleifera) leaves which Extracted Using Soxhletation Technique has been carried out. This research aims to determine what types of secondary metabolites are contained in Moringa leaves using soxhletation technique and the antioxidant activity of Moringa leaves extracted using soxhletation technique. The secondary metabolites contained in the methanol extract of Moringa leaves were determined by the phytochemical method, while the antioxidant activity was tested by the DPPH method. Moringa leaves used are dried Moringa leaves which have been mashed. Total of 150 g of Moringa leaves were soxhelated for 7 hours with methanol as solvent. Then the extracts were collected and concentrated to obtain a thick extract of 30.624 g. The extracts were tested for phytochemicals and antioxidants. Phytochemical test results showed that the methanol extract of Moringa leaves extracted using the soxhletation technique contained alkaloids, flavonoids, steroids, Polifenols and saponins. Moringa leaves methanol extract extracted using the soxhletation technique has very weak antioxidant activity with an IC50 value of 857.6894 ppm.